Penerapan Konsep Al-Uqud Al- Murakkabah atau Hybrid Contract pada Lembaga Keuangan Syariah - Siti Lutfiyah (CV. Ulil Albab Corp, 2023)
The growing economy with the various forms of transactions that occur in current conditions has resulted in a single contract no longer able to accommodate the public's needs for these transactions, especially in Islamic financial institutions. The existence of this multi-contract or hybrid contract is a product innovation to attract consumers to be more attractive so that it is demanded to be able to meet the needs of modern society which makes the combined contract in its application of two or more contracts in one transaction that cannot be separated from one another. The sharia economic literature continues to develop its theory where the original law does not allow two contracts to be made in one transaction, even though the prohibition is contained in the hadith relating to bai'ataini fi bai'atin; shafqataini in safqatin; and bai 'and salaf. This means that in practice, not all two contracts in one transaction are not allowed. However, the development of products that use hybrid contracts or multi-contracts by different scholars interpret the meaning of these hadiths so that it requires a study so that it is clearer the position or legal status of the multi-contracts that are often used so that they remain appropriate and do not violate the rules that have become an authoritative basis.